Reformas al Código de la Niñez y la Adolescencia, relacionado con la suspensión de la prestación de alimentos, cuando el cuidado y crianza del menor la realiza el progenitor alimentante - Elizalde Paladines, Yorky Raúl (2016)
The present thesis has artificial notability, because any topic, for much more or a lot less than it is the number of people involved in the problem they can be aided or abandoned respectively by the law, it is the case of those parents that when duplicating the payment from the nutritious pensions to them imposed, to be inmersos in the problem study matter they are in artificial indefensión, because a legal norm that allows to regulate this situation doesn't exist. It is of social transcendency, because it commits one of the sectors with more vulnerability indexes in the country like they are it the girls, children and adolescents, besides being a problem that has present time because the reclamation of the Right of Allowances has not stopped to have validity in the different Tribunals and Judicial Units of the Family, Woman, Childhood and domestic Adolescence. Problem without a doubt caused by the ullage of a standard that allows the suspension of the benefit of allowances, when the care and the boy's lactation, girl or adolescent for who was claimed allowances, the father carries out it to the one who judicial and in a first moment he was imposed the payment of an alimony, condition that puts in detriment the progenitor's economic capability that currently he has the care and the boy's lactation or girl or adolescent, and stiller, the minor upper interest is impaired consecrated in the Constitution, because when not existing money or when having a minimum quantity of this, you cannot satisfy the 5 boy's more indispensable requirements, girl or adolescent aided in the Constitution of the Republic. When opening the thematic one enunciated, he/she will have diverse approaches given for the benefit of allowances, everything it in accordance with the dispositions that the national juristic classification through the Civil Code and Organic Code of the Childhood and the Adolescence brings inside this topic, arguments that will be reinforced with the help of the comparative jurisprudence, this will allow to conclude with an appropriate interpretation of the results obtained in the field investigation, results that they will help to visualize in a better way the reality of the problem, using like socket the pansy and mainly the knowledge of the different professionals of the right to who you interviews and I interview, for this way to give the respective summations and recommendations and per ende an appropriate amendment proposal that it allows to revise the juristic hole.